2016
DOI: 10.1016/j.dadm.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment among World Trade Center responders: Long‐term implications of re‐experiencing the 9/11 terrorist attacks

Abstract: IntroductionDuring the World Trade Center (WTC) attacks, responders who helped in search, rescue, and recovery endured multiple traumatic and toxic exposures. One-fifth subsequently developed post-traumatic stress disorder (PTSD). PTSD has been linked to dementia in veterans. This study examined the association between WTC-related PTSD and cognitive impairment (CI) in WTC responders.MethodsA one-third sample of responders (N = 818) reporting for annual monitoring visits were screened for cognitive impairment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
116
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 68 publications
(127 citation statements)
references
References 43 publications
9
116
2
Order By: Relevance
“…A second possibility is that PTSD may result in increased neurodegeneration. Prior work has detailed similar increases in PTSD symptoms among people with cognitive impairments (Clouston et al, 2016). Of particular concern, a shared pattern of physical and cognitive impairment co-occurring with increases in emotionality may signal the potential for an increased risk of neurodegenerative diseases in general and may, specifically, highlight an elevated potential for behavioral frontotemporal dementia (FTD), a neurodegenerative disease that can include behavioral and emotional changes alongside physical impairments (Mackenzie, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A second possibility is that PTSD may result in increased neurodegeneration. Prior work has detailed similar increases in PTSD symptoms among people with cognitive impairments (Clouston et al, 2016). Of particular concern, a shared pattern of physical and cognitive impairment co-occurring with increases in emotionality may signal the potential for an increased risk of neurodegenerative diseases in general and may, specifically, highlight an elevated potential for behavioral frontotemporal dementia (FTD), a neurodegenerative disease that can include behavioral and emotional changes alongside physical impairments (Mackenzie, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Since then, researchers have linked WTC exposures to various health problems, including increased risk of asthma (Wisnivesky et al., ) and gastrointestinal issues (Li et al., ), to name a few. Yet despite the high burden of cognitive impairment, lowered pulmonary functioning, and systemic inflammation in this population (Aldrich et al., ; Clouston et al., ; Kazeros et al., ), little is known about the burden of functional limitations among WTC responders.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Prior analyses have found that the SBU clinic monitors responders who are similar in terms of exposures, PTSD burden, and age on 9/11/2001 to the responder population [1]. In 2014, SBU began the first and only prospective study to date to assess indicators of aging in WTC responders by incorporating cognitive assessments into the monitoring visit [18].…”
Section: Methodsmentioning
confidence: 99%
“…Research studies of WTC responders have found impairments in cognitive and physical functioning in this population [16][17][18], which is concentrated among responders reporting high levels of chronic intrusive re-experiencing stress. In addition, early reports have identified a small association between lengthy exposures to the pile/pit and cognitive dysfunction [17].…”
mentioning
confidence: 89%